Investigating Use of a Parent Report Tool to Measure Vocabulary Development in Deaf Greek-speaking Children with Cochlear Implants - Oktapoti, Maria; Okalidou, Areti; Kyriafinis, George; Petinou, Kakia; Vital, Victor; Herman, Rosalind (My University, 2016)
Objective: There are very few measures of language development in spoken Greek that can be used with young deaf children. This study investigated the use of Cyprus Lexical List (CYLEX), a receptive and expressive vocabulary assessment based on parent report that has recently been adapted to Standard Greek, to measure the vocabulary development of deaf Greek-speaking children with cochlear implants. Design: A Standard Greek version of CYLEX was used to collect data on receptive and expressive vocabulary development from parents of thirteen deaf children with cochlear implants aged between 21 and 71 months. These data were compared with data collected previously from typically developing hearing Greek-speaking children. Results: Use of the test by parents of deaf children was found to be reliable. No correlation was found between children's vocabulary scores and chronological age. A positive correlation was however found between children's post-implant age and expressive vocabulary. The vocabulary skills of implanted children with a mean post-implant age of 20 months were not significantly different from those of typically developing hearing children of similar chronological age. Conclusion: CYLEX is a reliable and useful tool for exploring vocabulary development with this clinical group. Findings confirm the results of other studies in indicating that the vocabulary size of implanted pre-school-aged deaf children is related to the amount of time that children have used their implant, rather than chronological age.
Keywords: Deaf children; Cochlear implants; Vocabulary; Language assessment; Parent-report